Distributed Computing and Internet Technology 7th International Conference, ICDCIT 2011, Bhubaneshwar, India, February 9-12, 2011, Proceedings - Natarajan, Raja.; Natarajan, Raja.; Ojo, Adegboyega.; Ojo, Adegboyega. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
This book constitutes the proceedings of the 7th International Conference on Distributed Computing and Internet Technology, ICDCIT 2011, held in Bhubaneswar, India, in February 2011. The 18 papers presented in this volume were carefully reviewed and selected from 138 submissions. In addition the book contains the full versions of 6 invited talks. The papers are grouped in topical sections on distributed computing, sensor networks, internet technologies and applications, security, and bio-inspired computing.